Rapor Pendidikan Analisis Rapor Pendidikan Sebagai Dasar Penyusunan Program Berbasis Data : Studi Kasus di SMPN 3 Kualatungkal dan SMPN Satap 7 Pengabuan - Budi Teguh Harianto (Balitbangda Provinsi Jambi, 2023)
The Data Based Program (PBD) is a new breakthrough by the government. Referring to the education report card, of course PBD is a new tool that really helps educational units solve various problems they face. This study seeks to describe the understanding of policy makers in analyzing educational report cards for PBD basis. This research is a case study in two schools, SMPN 3 Kualatungkal and SMPN Satap 7 Pengabuan, two schools with different characteristics. From the results of the study, it was found that both school principals were able to understand and analyze education report cards as a basic reference for PBD. The program created is a recommendation from an analysis of educational report cards, especially to increase the achievement of minimum competency in literacy and numeracy indicators. Numerical competence with less information means that it is necessary to increase the ability of educators to carry out student-based learning. While the literacy indicator at SMPN Satap 7 is less with a percentage of 11.76 percent, students who achieve minimum competency. Meanwhile, at SMPN 3, the competence score was moderate, with a percentage score of 53.33 percent having achieved minimum competency. The Independent Teaching Platform (PMM) and being active in the MGMP organization is one solution to solving the problem. The addition of learning support facilities such as reading books and references is also a program compiled by the school. While the character indicators, both schools with moderate predicate.